HIV subtype, epidemiological and mutational correlations in patients from Paraná, Brazil - Silva,Monica Maria Gomes da (2010)
OBJECTIVE: Analyze patients with HIV infection from Curitiba, Paraná, their epidemiological characteristics and HIV RAM. METHODS: Patients regularly followed in an ID Clinic had their medical data evaluated and cases of virological failure were analyzed with genotypic report. RESULTS: Patients with complete medical charts were selected (n = 191). Demographic and clinical characteristics were compared. One hundred thirty two patients presented with subtype B infection (69.1%), 41 subtype C (21.5%), 10 subtype F (5.2%), 7 BF (3.7%) and 1 CF (0.5%). Patients with subtype B infection had been diagnosed earlier than patients with subtype non-B. Also, subtype B infection was more frequent in men who have sex with men, while non-B subtypes occurred more frequently in heterosexuals and women. Patients with previous history of three classes of ARVs (n = 161) intake were selected to evaluate resistance. For RT inhibitors, 41L and 210W were more frequently observed in subtype B than in non-B strains. No differences between subtypes and mutations were observed to NNTRIs. Mutations at 10, 32 and 63 position of protease were more observed in subtype B viruses than non-B, while positions 20 and 36 of showed more amino acid substitutions in subtype non-B viruses. Patients with history of NFV intake were evaluated to resistance pathway. The 90M pathway was more frequent in subtypes B and non-B. Mutations previously reported as common in non-B viruses, such as 65R and 106M, were uncommon in our study. Mutations 63P and 36I, previously reported as common in HIV-1 subtypes B and C from Brazil, respectively, were common. CONCLUSION: There is a significant frequency of HIV-1 non-B infections in Paraná state, with isolates classified as subtypes C, F, BF and BC. Patients with subtype C infection were more frequently female, heterosexual and had a longer average time of HIV diagnosis